(untitled) (Journal of Multidisciplinary Sciences and Innovations, 2025)
This article analyzes the complex process of artistic transformation from word to poetic image based on deep scientific-theoretical and practical approaches. The transformation of the word from a simple means of communication into an artistic-aesthetic image is considered inextricably linked with thought, feeling and cultural consciousness. Initially, the word, which is condensed in content in the lexical -spiritual layer, acquires new semantic possibilities in the context of a poetic text; it comes to life with the help of rhythm, melody, syntactic organization and aesthetic means and turns into a poetic image. In this process, the word itself goes beyond its initial lexical meaning and rises to the level of an image with a multi-layered meaning, symbolic load and emotional impact. The spiritual and aesthetic resonance of the word in each poetic unit, its role in the perception of feelings, and its transformational role in figurative thinking were analyzed. The scientific significance of the article is that it considers the poetic image as a phenomenon of an open and dynamic nature, recreating not only within the literary text, but also in the reader’s mind. On this basis, the article develops an integrative theoretical and practical model that consistently illuminates the process from word to image.